2005
DOI: 10.1002/j.2050-0416.2005.tb00665.x
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Contamination, Toxicity and Quality of Turned and Unturned Outdoor Floor Malted Sorghum

Abstract: Turned and unturned outdoor floor malted sorghum were studied for their total microbial contamination, nature and extent of contamination by moulds, cytotoxicity (IC 50 ) and quality in terms of diastatic power (DP). The presence of aflatoxins, fumonisins, deoxynivalenol and zearalenone were also investigated. Total microbial counts were high (10 7 -10 8 cfu /g) in both turned and unturned samples. All samples showed contamination by different moulds, with the dominant being Mucor species, Rhizopus oryzae, Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
1
12
2
Order By: Relevance
“…This is in apparent contradiction to the results in our previous work 8 . However, in that case the steep water was not changed, whereas it was changed twice during malting in this work.…”
Section: Mycotoxins and Cytotoxicitycontrasting
confidence: 99%
See 2 more Smart Citations
“…This is in apparent contradiction to the results in our previous work 8 . However, in that case the steep water was not changed, whereas it was changed twice during malting in this work.…”
Section: Mycotoxins and Cytotoxicitycontrasting
confidence: 99%
“…Therefore, there is a need for efficient and safe ways to control microbial growth during sorghum malting. As shown in our previous work 8 , the physical measure of turning germinating grains did not result in inhibited microbial growth. Steeping is probably the most critical stage at which microbial proliferation begins 10 .…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Two condensed tannin-free red sorghum cultivars, NK 283 and PAN 8546 were used as described in our previous work 16,17 .…”
Section: Sorghum Grainmentioning
confidence: 99%
“…Traditional outdoor floor malted sorghum can be contaminated with high levels of coliform bacteria and moulds that can potentially produce mycotoxins 17 . Recently we have shown that these undesirable sorghum malt microflora can be controlled by steeping in dilute NaOH 16 .…”
Section: Introductionmentioning
confidence: 99%